European Journal of Transport and Infrastructure Research 2021
DOI: 10.18757/ejtir.2021.21.1.5135
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 lockdown on commuting

Abstract: We carried out an international online survey about changes in everyday mobility during the COVID-19 outbreak in 21 languages, collecting more than 11,000 responses from more than 100 countries. In this paper, we present our analysis about commuting travels of the responses between 23 March and 12 May 2020 from the fourteen countries with 100 or more responses, namely Austria, Brazil, Bulgaria, Czechia, Germany, Hungary, Iran, Italy, Japan, Malaysia, Slovakia, Slovenia, Thailand, and the UK. Home office is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 22 publications
1
22
0
4
Order By: Relevance
“…Many countries (e.g., the United States, France, and Italy) implemented mandatory lockdowns, limiting all nonessential travel (Haas et al, 2020; Shibayama et al, 2021 , Xiong et al, 2020 ). In contrast, the Japanese government declared a state of emergency in April and May 2020, urging people to stay at home and refrain from nonessential outings.…”
Section: Introductionmentioning
confidence: 99%
“…Many countries (e.g., the United States, France, and Italy) implemented mandatory lockdowns, limiting all nonessential travel (Haas et al, 2020; Shibayama et al, 2021 , Xiong et al, 2020 ). In contrast, the Japanese government declared a state of emergency in April and May 2020, urging people to stay at home and refrain from nonessential outings.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Finbom et al (2020), participants from Germany reported a mode shift from public transport (bus, tram, and metro) to car, bicycling, and walking. In the study of Shibayama et al (2021), a large shift from public transport to home office was noticed, but some participants also reported shifting to car and bicycling. In the April/May 2021 panel of DLR Transport, 53% of participants reported using public transport less or much less, whereas walking (+26%), bicycling (+18%), and car (+14%) usage had increased.…”
Section: Introductionmentioning
confidence: 99%
“…Protection motivation theory (Rogers, 1975;Floyd et al, 2000) suggests that risk perception might have played a role in these trends concerning the use of public transport: Since the beginning of the pandemic, public transport was stigmatized as an infectious space in public health communication campaigns (Tirachini and Cats, 2020). The perception of public transport as a high-risk environment might have triggered protection motivation in form of a general avoidance of traveling (Zheng et al, 2021) and a specific avoidance of public transport (e.g., Finbom et al, 2020;Shibayama et al, 2021;DLR Transport, 2022b). A positive relationship between risk perception and protective behavior is already known from other pandemics and infectious disease outbreaks (for a review, see Bish and Michie, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many studies around the globe, i.e., China [10,11], Italy [12], Australia [13], Sweden [14], Spain [15], the United States [16], Pakistan [9], Germany [17][18][19], Greece [20], Jordan [21], and Turkey [1], have been focusing on the variations in people's mobility and travel behavior during COVID-19. Past studies pointed out that trip frequencies, travel duration, mode choice, commuting, and public transport usage worldwide have been receiving adverse effects of the COVID-19 pandemic [22,23]. A review of previous studies highlights that few modeling efforts have been conducted in the past to explore the relationship among mobility behaviors (travel trips by modes and by purposes), sociodemographic, and COVID-19 severity periods.…”
Section: Introductionmentioning
confidence: 99%